2002
DOI: 10.1207/s15327078in0301_5
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expressivity at 4 Months: A Context by Expression Analysis

Abstract: The specificity predicted by differential emotions theory (DET) for early facial expressions in response to 5 different eliciting situations was studied in a sample of 4-month-old infants (n = 150). Infants were videotaped during tickle, sour taste, jack-in-the-box, arm restraint, and maskedstranger situations and their expressions were coded second by second. Infants showed a variety of facial expressions in each situation; however, more infants exhibited positive (joy and surprise) than negative expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(22 citation statements)
references
References 63 publications
3
19
0
Order By: Relevance
“…Like Stenberg and Campos (1990), we found that MAX-specified anger expressions were the most common brow-mouth configuration produced during arm restraint. Like Bennett et al (2002) in their study of 4-month-old infants, we found that this was also the most common negative brow-mouth configuration produced in response to a fear elicitor. Our results differ only slightly from Bennett et al's (2005) findings for older infants.…”
Section: Discussionsupporting
confidence: 83%
“…Like Stenberg and Campos (1990), we found that MAX-specified anger expressions were the most common brow-mouth configuration produced during arm restraint. Like Bennett et al (2002) in their study of 4-month-old infants, we found that this was also the most common negative brow-mouth configuration produced in response to a fear elicitor. Our results differ only slightly from Bennett et al's (2005) findings for older infants.…”
Section: Discussionsupporting
confidence: 83%
“…According to one set of theories, the full set of emotion concepts is built up slowly through a process of differentiation (e.g., Bennett et al, 2002;Bridges, 1930;Fischer, 1980;Widen & Russell, 2003, 2008a, 2008b. By "differentiation," we mean that the child initially conceptualizes emotions in terms of very broad categories and then subdivides each category until eventually the full adult taxonomy is reached.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of decrease of mixed expressions and less intense expressions with age in response to at least some contexts (Bennett, Bendersky, & Lewis, 2002, 2005; Izard & Abe, 2004). Negative expressions and/or components associated with putative anger, sadness and fear have shown the least evidence of specificity although the number of contexts studied is still limited (Bennett et al, 2002, 2004). There is only limited evidence for correspondence between specific negative emotion states and specific contexts; for example, anger to contingency blockage reliably elicits anger expressions in most infants (Sullivan and Lewis, 2003).…”
Section: Assessment: Debate With Little Forward Momentummentioning
confidence: 99%
“…Although morphologically stable from 3 months of age (Izard, 1995, 1997), infant facial expressions are often fleeting. Infants also often show mixed expressions and some expressions unique to infancy in addition to full face configurations to specific eliciting contexts (Bennett, Bendersky, & Lewis, 2002; Matais & Cohen, 1993). There is evidence of decrease of mixed expressions and less intense expressions with age in response to at least some contexts (Bennett, Bendersky, & Lewis, 2002, 2005; Izard & Abe, 2004).…”
Section: Assessment: Debate With Little Forward Momentummentioning
confidence: 99%
See 1 more Smart Citation